2018
DOI: 10.1080/09637486.2018.1452900
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary flavonoids intake and obesity in a cohort of adults living in the Mediterranean area

Abstract: Dietary polyphenols, including flavonoids, are abundantly present in a healthy and balanced diet. Evidence for their role in preventing non-communicable diseases is emerging. We examined the association between estimated habitual intake of dietary flavonoid and obesity in a cohort study. After adjusting for potential confounding factors, inverse association between total flavonoid intake and excess weight (BMI ≥25) was found (OR = 0.66, 95% CI: 0.45, 0.99); among individual classes of flavonoids, only flavanon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 51 publications
1
40
0
1
Order By: Relevance
“…Similarly, a study conducted in the Mediterranean area demonstrated that higher dietary intake of flavonoids is inversely associated with an excess of weight and obesity [ 29 ]. Studies conducted in non-Mediterranean areas have shown an effect of polyphenol intake on weight control, but other clinical trials did not find any relationship between polyphenol intake and weight loss or changes in body composition (CITA).…”
Section: Antiobesity Effects Of Dietary Polyphenolsmentioning
confidence: 99%
“…Similarly, a study conducted in the Mediterranean area demonstrated that higher dietary intake of flavonoids is inversely associated with an excess of weight and obesity [ 29 ]. Studies conducted in non-Mediterranean areas have shown an effect of polyphenol intake on weight control, but other clinical trials did not find any relationship between polyphenol intake and weight loss or changes in body composition (CITA).…”
Section: Antiobesity Effects Of Dietary Polyphenolsmentioning
confidence: 99%
“…In addition, dairy products have been reported to be part of a healthy Mediterranean dietary pattern which, together with lower sodium consumption, may ameliorate cardiovascular risk [63,64]. Moreover, several plant-foods commonly consumed, including those previously listed together with (red) wine, are rich in phytochemicals with antioxidant and anti-inflammatory properties, which may prevent or counteract the subclinical low-grade inflammation occurring with impaired body weight, metabolism, and generally considered the first pathogenic process occurring in cardio-metabolic disorders [65,66]. Among them, polyphenols have been among the most studied recently and have been associated with decreased risk of mortality (especially from CVD) as well as inversely associated with occurrence of type-2 diabetes, hypertension, and metabolic disorders [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Besides polyphenols, antioxidant vitamins were correlated with total water intake, and specifically with water from food. This suggests that foods with a high content of water, like fruits and some kinds of vegetables, are the main source of these substances [ 60 , 61 , 62 ]. As expected, correlations between vitamin C and fruit juices, and vitamin B12 and milk were found, suggesting that such beverages are among the major sources of these vitamins.…”
Section: Discussionmentioning
confidence: 99%